Meeting the Challenge of Cancer Survivorship in Public Health: Results from the Evaluation of the Chronic Disease Self-Management Program for Cancer Survivors - Betsy C. Risendal; Andrea Dwyer; Richard W. Seidel; Kate Lorig; Letoynia Coombs; Marcia G. Ory (Frontiers Media S.A., 2015)
IntroductionSelf-management has been identified as an important opportunity to improve health outcomes among cancer survivors. However, few evidence-based interventions are available to meet this need.MethodsThe effectiveness of an adapted version of the Chronic Disease Self-Management Program for cancer survivors called Cancer Thriving and Surviving was evaluated in a randomized trial. Outcomes were assessed at baseline and 6-months post program via written survey among 244 participants in Colorado. Repeated measures analysis was used to analyze pre/post program change.ResultsStatistically significant improvement was observed among those in the intervention in the following outcomes: Provider communication (+16.7% change); depression (−19.1%); energy (+13.8%); sleep (−24.9%) and stress-related problems (−19.2%); change over time was also observed in the controls for energy, sleep, and stress-related outcomes though to a lesser degree. Effect sizes of the difference in change over time observed indicate a net beneficial effect for provider communication (0.23); and decreases in depression (−0.18); pain (−0.19); problems related to stress (−0.17); and sleep (−0.20).ConclusionStudy data suggest that the self-management support from adaptation of the CDSMP can reach and appeal to cancer survivors, improves common concerns in this population, and can fill an important gap in meeting the ongoing need for management of post-diagnosis issues in this growing segment of the U.S. population.